2008
DOI: 10.1016/j.physletb.2008.01.071
|View full text |Cite
|
Sign up to set email alerts
|

Higgs boson masses in the MSSM with general soft breaking

Abstract: The operators that break supersymmetry can be holomorphic or non-holomorphic in structure. The latter do not pose any problem for gauge hierarchy and are soft provided that the particle spectrum does not contain any gauge singlets. In minimal supersymmetric model (MSSM) we discuss the impact of non-holomorphic soft-breaking terms on the Higgs sector. We find that non-holomorphic operators can cause significant changes as are best exhibited by the correlation between the masses of the charginos and Higgs boson

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…Analyses that particularly focussed on the Higgs sector and constraints like Br(B → X s +γ) are refs. [56,57]. However, in contrast to ref.…”
Section: Jhep10(2016)027mentioning
confidence: 58%
See 1 more Smart Citation
“…Analyses that particularly focussed on the Higgs sector and constraints like Br(B → X s +γ) are refs. [56,57]. However, in contrast to ref.…”
Section: Jhep10(2016)027mentioning
confidence: 58%
“…However, in contrast to ref. [56] that used input parameters given entirely at the unification scale, ref. [57] analyzed in a mixed set-up where the NH parameters were given at the electroweak scale in an otherwise CMSSM type of setup.…”
Section: Jhep10(2016)027mentioning
confidence: 99%
“…Staying within an MSSM setup terms like φ 2 φ * or a higgsino mass term like ψψ can be soft SUSY breaking in nature if there is no presence of a gauge singlet field [71]. There have been several works over the past two decades [69][70][71][72][73][74][75][76][77][78][79][80][81][82] that analyzed the effects of introducing NH soft terms. 2 There are three distinct signatures i) the trilinear NH terms may enhance L-R mixing thus influencing various phenomenologies, ii) higgsinos get an additional soft-term source, iii) the Higgs potential remains unaffected at the tree level thus electroweak fine-tuning may hardly change.…”
Section: Jhep01(2018)158mentioning
confidence: 99%
“…2 There are three distinct signatures i) the trilinear NH terms may enhance L-R mixing thus influencing various phenomenologies, ii) higgsinos get an additional soft-term source, iii) the Higgs potential remains unaffected at the tree level thus electroweak fine-tuning may hardly change. The latter effect can give rise to a valid higgsino dark matter with low fine-tuning, whereas the L-R mixing effect may contribute to (g − 2) µ , Br(B → X s + γ), or the higgs mass radiative corrections [69,70,[78][79][80][81]. The NH soft terms can also influence on the scalar potential terms involving colored/charged scalars [82].…”
Section: Jhep01(2018)158mentioning
confidence: 99%
“…It has been shown that in the absence of any gauge singlet it is possible to extend the SUSY breaking soft sector by including NH soft SUSY breaking terms, without aggravating any quadratic divergence [71,74,80]. Thus, the NH soft terms of the NHSSM in general that include trilinear coupling terms as well as a NH higgsino mass (µ ) term are given by [33,83] …”
Section: Ccb In Nhssmmentioning
confidence: 99%